Genomic and comparative clinico-pathological assessment of two Pakistani pigeon-derived newcastle disease virus sub-genotypes XXI.1.1 and XXI.1.2 isolated in 2017. (March 2023) - Ather, Safa; Wajid, Abdul; Batool, Andleeb; Noureen, Aasma; Ain, Quratul; Ayub, Goher; Molouki, Aidin; Sultan, Imrana Niaz; Mahmood, Sara; Hanif, Atif; Ahmed, Nazeer
Abstract: Pigeon paramyxovirus type-1 (PPMV-1) is an antigenic-variant of Newcastle disease virus (NDV) which is associated with infection in Columbidae family. In this study, we isolated two pigeon-derived strains pi/Pak/Lhr/SA_1/17 (designed as SA_1) and pi/Pak/Lhr/SA_2/17 (designed as SA_2) from diseased pigeons collected in Punjab province in 2017. We performed the whole genome, phylogenetic analysis and comparative clinico-pathological evaluation of two viruses in pigeons. Phylogenetic analysis based on fusion ( F ) gene and complete genome sequences showed that SA_1 belonged to sub-genotype XXI.1.1 and SA_2 clustered in sub-genotype XXI.1.2. SA_1 and SA_2 viruses contributed to morbidity and mortality in pigeons. Remarkably, although the two viruses resulted in comparatively similar pattern of pathogenesis and replication ability in various tissues of infected pigeons, SA_2 could cause more severe histopathological lesions and had comparatively high replication ability in pigeons than SA_1. Moreover, pigeons infected with SA_2 had higher shedding efficiency than that of pigeons infected with SA_1. Moreover, several aa substitutions in the major functional domains of the F and HN proteins might be contributed to the pathogenic differences between the two isolates in pigeons. Overall, these findings provide us with important insight into the epidemiology and evolution of PPMV-1 in Pakistan and laid the foundation for the further elucidation of the mechanism underlying the pathogenic difference of PPMV-1 in pigeons. Highlights: A complete genome sequence of sub-genotype XXI.1.2, genotype XXI of class II, is reported for the first time. Preliminary report of comprehensive genomic analysis and comparative clinico-pathological assessment of XXI.1.1 and XXI.1.2 viruses in pigeons. The XXI.1.2 viruses had comparatively greater pathogenicity level, replication ability and shedding efficiency than XXI.1.1 viruses. The information obtained from this study could be helpful in preventive measures including developing an effective vaccine against PPMV-1 in Pakistan.